Interdisciplinary approaches in Humanities: A modern perspective - Sapra, Amrapali Chawla (AG Volumes, 2025)
In the modern world that is becoming more globalised, the exchange of cultural knowledge (including ideas, concepts, imaginative forms, and techniques) is not only beneficial for creative interactions, but also for facilitating "cross-cultural tensions or misunderstandings". Interdisciplinary research that may bridge the cultural divide across disparate disciplines and areas of study is becoming more and more in demand as a result of the humanities’ present research that promotes cross-cultural academic knowledge exchange. This article review examines the many studies on interdisciplinary methods in the humanities that have been conducted. This review highlights that interdisciplinary approaches in the humanities have evolved significantly with the integration of digital tools, big data, and artificial intelligence. Digital humanities education now emphasizes not only technical proficiency but also the fusion of diverse disciplinary knowledge and practical application. Courses across universities reflect this trend, offering training in text analysis, digital publishing, and spatial humanities. The convergence of traditional humanities with fields like data science and IT fosters broader perspectives and innovative solutions to complex social issues. By bridging disciplines such as philosophy, linguistics, and literature, interdisciplinary research enhances dialogue and expands the scope of humanistic inquiry.